A multiscale classification of urban morphology - Patrick Michael Schirmer; Kay W. Axhausen (Journal of Transport and Land Use)
Various studies in the field of urban planning and design have given recommendations for "good urban forms," suggesting that specific spatial characteristics inform the quality of an urban landscape and the way people perceive and behave in them. When modeling spatial behavior in the form of location choice models or hedonic prices, we should reflect these spatial characteristics through the integration of quantitative attributes such as model variables, which is currently only done in a very limited way.